Sport fans’ behaviour : the relationship between nostalgia, team loyalty, attitude toward sponsors, and behavioural intentions - Tan, Doreen Xiaofang (2019)
European football is one of the most popular sports in the world. Spectators enjoy football for the aspects of self-identity, socialisation, and rituals among other factors. These characteristics of football create an appropriate environment for nostalgia. Previous studies have found that nostalgia can lead to team loyalty, positive attitude toward sponsors, and behavioural intentions like travelling to attend sport events or purchasing a sponsor’s products. The current study aims to build a research model that connects the four constructs and determine if nostalgia has an effect on fan loyalty, attitude toward sponsors, and future behavioural intentions. A total of 317 European football league fans in Singapore participated in the study by completing an online questionnaire. Data were then screened using Statistical Package for the Social Science, and further analysed through Confirmatory Factor Analysis and Structural Equation Modelling using Analysis of Moment Structure. Results showed significant relationships for the following: nostalgia on team loyalty (H1: 0.615, p=0.001), attitude toward sponsors (H2: 0.557, p=0.001), and behavioural intentions (H3: 0.280, p=0.004), team loyalty on attitude toward sponsors (H4: –0.138, p=0.003), and attitude toward sponsors on behavioural intentions (H6: 1.077, p<0.001). Furthermore, team loyalty and attitude toward sponsors partially mediate between nostalgia and behavioural intentions (H7: –0.770, p=0.001). These findings will allow organisations to understand that nostalgia, team loyalty, and attitude toward sponsors are needed as driving factors for football fans to visit the home grounds of football clubs or purchase sponsor products, as well as better predict fans’ behaviour, needs, and demands.